Congenital dermatofibrosarcoma protuberans with fibrosarcomatous and myxoid change. Issue 9 (26th August 2005) - Gu, W; Ogose, A; Kawashima, H; Umezu, H; Kudo, N; Hotta, T; Endo, N
Abstract : This report describes a case of congenital dermatofibrosarcoma protuberans (DFSP) with fibrosarcomatous (FS) and myxoid areas. Immunohistochemical results showed that tumour cells in ordinary DFSP areas were diffusely positive for CD34, whereas in the FS and myxoid areas, few tumour cells were positive for this antigen. Ki-67 positive tumour cell numbers were greater in the FS (11.8%) and myxoid areas (19.8%) relative to ordinary DFSP areas (2.2%). Reverse transcription polymerase chain reaction and sequence analysis showed the presence of an identical COL1A1–PDGFB fusion transcript in ordinary DFSP (plaque-like area), FS, and myxoid areas of DFSP. These results indicate that the three components of DFSP have a common histogenesis. This study documents the first application of gene analysis involving the myxoid area of DFSP.